88.3k views
0 votes
(Show your working) I uploaded the question

(Show your working) I uploaded the question-example-1

1 Answer

5 votes

x^2 = the first integer

(x - 1)^2 = the second integer.

x^2 - (x - 1)^2 = ?

First, let's plug a number into our equation for x.

(2)^2 - (2 - 1)^2 = ?

4 - (1)^2 = ?

4 - 1 = 3

As we can see the difference is odd but it's also the sum of the two consecutive integers.

2 + 1 = 3.

This works for all numbers. Let's plug another number into our equation for x.

(4)^2 - (4 - 1)^2 = ?

16 - (3)^2 = ?

16 - 9 = 7

4 + 3 = 7

Try any number and it will always be odd.

User HadleyHope
by
5.0k points